Identification of fracture toughness parameters to understand the fracture resistance of advanced high strength sheet steels. (15th April 2020) - Frómeta, D.; Parareda, S.; Lara, A.; Molas, S.; Casellas, D.; Jonsén, P.; Calvo, J.
Highlights: The fracture toughness of four advanced high strength steel sheets is evaluated. J-integral, essential work of fracture and Kahn tear tests are performed. The differences between the different fracture resistance parameters is discussed. The effect of specimen geometry and notch radius on fracture toughness is analysed. we is a suitable property to predict the fracture performance of AHSS sheets. Abstract: The fracture toughness of four advanced high strength steel (AHSS) thin sheets is evaluated through different characterization methodologies, with the aim of identifying the most relevant toughness parameters to describe their fracture resistance. The investigated steels are: a Complex Phase steel, a Dual Phase steel, a Trip-Aided Bainitic Ferritic steel and a Quenching and Partitioning steel. Their crack initiation and propagation resistance is assessed by means of J-integral measurements, essential work of fracture tests and Kahn-type tear tests. The results obtained from the different methodologies are compared and discussed, and the influence of different parameters such as specimen geometry or notch radius is investigated. Crack initiation resistance parameters are shown to be independent of the specimen geometry and the testing method. However, significant differences are found in the crack propagation resistance values. The results show that, when there is a significant energetic contribution from necking during crack propagation, the specific essential work of fracture ( we ) better describes the overall fracture resistance of thin AHSS sheets than JC . In contrast, energy values obtained from tear tests overestimate the crack propagation resistance and provide a poor estimation of AHSS fracture performance. we is concluded to be the most suitable parameter to describe the global fracture behaviour of AHSS sheets and it is presented as a key property for new material design and optimization.